Evaluation of the shucking of certain species of scallops contaminated with lipophilic toxins with a view to the production of edible parts meeting the safety requirements foreseen in the Union legislation. (9th March 2021) - ,; Schrenk, Dieter; Bignami, Margherita; Bodin, Laurent; del Mazo, Jesús; Grasl‐Kraupp, Bettina; Hogstrand, Christer; Chipman, Kevin James; Leblanc, Jean‐Charles; Nebbia, Carlo Stefano; Nielsen, Elsa; Ntzani, Evangelia; et al.
Abstract: EFSA was asked by the European Commission to provide information on levels of lipophilic shellfish toxins in whole scallops that would ensure levels in edible parts below the regulatory limits after shucking, i.e. removal of non‐edible parts. This should include the okadaic acid (OA), the azaspiracid (AZA) and the yessotoxin (YTX) groups, and five species of scallops. In addition, EFSA was asked to recommend the number of scallops in an analytical sample. To address these questions, EFSA received suitable data on the three toxin groups in two scallop species, Aequipecten opercularis and Pecten maximus, i.e. data on individual and pooled samples of edible and non‐edible parts from contamination incidents. The majority of the concentration levels were below limit of quantification (LOQ)/limit of detection (LOD), especially in adductor muscle but also in gonads. Shucking in most cases resulted in a strong decrease in the toxin levels. For Pecten maximus, statistical analysis showed that levels in whole scallops should not exceed 256 μg OA eq/kg or 217 μg AZA1 eq/kg to ensure that levels in gonads are below the regulatory limits of 160 μg OA or AZA1 eq/kg with 99% certainty. Such an analysis was not possible for yessotoxins or any toxin in Aequipecten opercularis and an assessment could only be based on upper bound levels. To ensure a 95% correct prediction on whether the level in scallops in an area or lot is correctly predicted to be compliant/non‐compliant, it was shown that 10 scallops per sample would be sufficient to predict with 95% certainty if levels of OA‐group toxins in the area/lot were 25% below or above the regulatory limit. However, to predict with a 95% certainty for levels between 140 and 180 μg OA eq/kg, a pooled sample of more than 30 scallops would have to be tested.